Effect of Intra-amniotic Oestriol Sulphate on Uterine Contractions. Issue 5660 (28th June 1969) - Klopper, A. I.; Dennis, K. J.; Farr, Valerie
Abstract : The effects of oestriol sulphate on myometrial activity in a group of young primigravidae, who were at 41 or more weeks' gestation, are compared with those of a placebo in a double-blind trial. Both compounds were administered over a period of six hours directly into the uterine cavity following artificial rupture of membranes. Intra-amniotic pressure recordings demonstrated a peak in the mean intensity in uterine contractions in the oestriol-treated and placebo-treated groups at six and four hours, respectively. The length of labour tended to be shorter in those patients having greater uterine activity.